Search for charged Higgs bosons in the H-+/- -> tau(+/-)nu(tau) decay channel in proton-proton collisions at s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Dragicevic,M; Eroe,J; Del,Valle AE; Flechl,M; Fruehwirth,R; et al. (JOURNAL OF HIGH ENERGY PHYSICS, 2019)
A search is presented for charged Higgs bosons in the H± → τ±ντ decay mode in the hadronic final state and in final states with an electron or a muon. The search is based on proton-proton collision data recorded by the CMS experiment in 2016 at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1. The results agree with the background expectation from the standard model. Upper limits at 95% confidence level are set on the production cross section times branching fraction to τ±ντ for an H± in the mass range of 80GeV to 3TeV, including the region near the top quark mass. The observed limit ranges from 6 pb at 80 GeV to 5 fb at 3 TeV. The limits are interpreted in the context of the minimal supersymmetric standard model mhhod − scenario.